Powerpath controller for fuel cell & battery hybridisation. (23rd February 2016) - Howroyd, Simon; Chen, Rui
Abstract: Proton Exchange Membrane (PEM) fuel cells are a chemically fuelled power supply which generally have a higher energy density than Lithium-Polymer Battery (LIPOs) but a much lower power density. In order for PEM fuel cells to increase the endurance of an in-service battery power supply, without decreasing the peak power, it should be hybridised with a battery. It is key for the market that the overall switch to hybrid technology is low cost in terms of size, weight and money. Hybrid technology tends to be generically designed to suit any power system, using regulators to ensure voltage matching, and diodes to control the direction of electrical flow. Many electric motors are controlled by speed controllers which can regulate the thrust provided by the motor, accounting for fluctuations in voltage usually found in a depleting battery. Using diode and regulator based hybrids for electric motor applications is therefore inherently inefficient even if complicated synchronous DC–DC converters are used due to the increased cost, size and weight. This paper demonstrates the ability to use ideal diodes to control the flow of electricity through the hybrid and that voltage regulation is not needed for a motor in this case. Furthermore, this paper explores the natural balancing strategy created by duty cycling the PEM fuel cell to different points within it's polarisation curve, removing the requirement for DC–DC converters to match it to the battery voltage. The changes made improve the efficiency of the hybrid power electronics to over 97%. Highlights: Switched mode regulators are not cost effective for PEM fuel cell battery hybrids. A PEM fuel cell will naturally balance with a battery to form a hybrid. A new hybrid system with less components and greater efficiency has been made. The PEM fuel cell outputs a steady current, the battery fills in the rest. Under low load the battery goes completely unused.